Noninvasive in vivo imaging of macrophages: understanding tumor microenvironments and delivery of therapeutics - Prakash Gangadaran; Akanksha Onkar; Ramya Lakshmi Rajendran; Anshika Goenka; Ji Min Oh; Fatima Khan; ArulJothi Kandasamy Nagarajan; Sathish Muthu; Anand Krishnan; Chae Moon Hong; Byeong-Cheol Ahn (Biomarker Research)
Abstract Macrophages are pivotal in the body’s defense and response to inflammation. They are present in significant numbers and are widely implicated in various diseases, including cancer. While molecular and histological techniques have advanced our understanding of macrophage biology, their precise function within the cancerous microenvironments remains underexplored. Enhancing our knowledge of macrophages and the dynamics of their extracellular vesicles (EVs) in cancer development can potentially improve therapeutic management. Notably, macrophages have also been harnessed to deliver drugs. Noninvasive in vivo molecular imaging of macrophages is crucial for investigating intricate cellular processes, comprehending the underlying mechanisms of diseases, tracking cells and EVs’ migration, and devising macrophage-dependent drug-delivery systems in living organisms. Thus, in vivo imaging of macrophages has become an indispensable tool in biomedical research. The integration of multimodal imaging approaches and the continued development of novel contrast agents hold promise for overcoming current limitations and expanding the applications of macrophage imaging. This study comprehensively reviews several methods for labeling macrophages and various imaging modalities, assessing the merits and drawbacks of each approach. The review concludes by offering insights into the applicability of molecular imaging techniques for real time monitoring of macrophages in preclinical and clinical scenarios.